European Restrictions on 1,2‐Dichloroethane: C−H Activation Research and Development Should Be Liberated and not Limited - Sherwood, James (Angewandte Chemie International Edition, 2018)
Plan B: 1,2‐Dichloroethane was recently subject to regulatory controls in the European Union that will severely limit its commercial use. The practitioners of innovative synthetic methods, particularly C−H bond activation, need to investigate alternative solvents if their chemistry is to stay relevant.